Theme-based vocabulary 1 - Kirkpatrick, Betty (Learners Publishing Pte Ltd, 2007)
This series of two books features a total of thirty essential themes related to areas of interes that are central to everyday life. It is vital that students understand and are able to apply the vocabulary related to these themes.